Effect of empirical treatment with moxifloxacin and meropenem vs meropenem on sepsis-related organ dysfunction in patients with severe sepsis: a randomized trial - Brunkhorst, Frank Martin; Büchler, Markus W. (The journal of the American Medical Association, 2012)
Context: Early appropriate antimicrobial therapy leads to lower mortality rates associated with severe sepsis. The role of empirical combination therapy comprising at least 2 antibiotics of different mechanisms remains controversial. Objective: To compare the effect of moxifloxacin and meropenem with the effect of meropenem alone on sepsis-related organ dysfunction. Design, Setting, and Patients: A randomized, open-label, parallel-group trial of 600 patients who fulfilled criteria for severe sepsis or septic shock (n = 298 for monotherapy and n = 302 for combination therapy). The trial was performed at 44 intensive care units in Germany from October 16, 2007, to March 23, 2010. The number of evaluable patients was 273 in the monotherapy group and 278 in the combination therapy group.Interventions: Intravenous meropenem (1 g every 8 hours) and moxifloxacin (400 mg every 24 hours) or meropenem alone. The intervention was recommended for 7 days and up to a maximum of 14 days after randomization or until discharge from the intensive care unit or death, whichever occurred first. Main Outcome Measure: Degree of organ failure (mean of daily total Sequential Organ Failure Assessment [SOFA] scores over 14 days; score range: 0-24 points with higher scores indicating worse organ failure); secondary outcome: 28-day and 90-day all-cause mortality. Survivors were followed up for 90 days. Results: Among 551 evaluable patients, there was no statistically significant difference in mean SOFA score between the meropenem and moxifloxacin group (8.3 points; 95% CI, 7.8-8.8 points) and the meropenem alone group (7.9 points; 95% CI, 7.5-8.4 points) (P = .36). The rates for 28-day and 90-day mortality also were not statistically significantly different. By day 28, there were 66 deaths (23.9%; 95% CI, 19.0%-29.4%) in the combination therapy group compared with 59 deaths (21.9%; 95% CI, 17.1%-27.4%) in the monotherapy group (P = .58). By day 90, there were 96 deaths (35.3%; 95% CI, 29.6%-41.3%) in the combination therapy group compared with 84 deaths (32.1%; 95% CI, 26.5%-38.1%) in the monotherapy group (P = .43). Conclusion: Among adult patients with severe sepsis, treatment with combined meropenem and moxifloxacin compared with meropenem alone did not result in less organ failure. Trial Registration: clinicaltrials.gov Identifier: NCT00534287
Gesehen am 18.09.2018